Rancang Bangun Sistem Informasi Perputaran Penjualan Barang Pada Toko Asri Busana Kebumen - Wibowo, Imaduddin Endri; Widodo, Arifin Puji; Ayuningtyas, Ayuningtyas (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Asri Busana store in the procurement of goods based on consumer interest. Procurement can’t run properly because the information obtained was limited to recapitulation the bill of sale, to determine consumer interest so far only based on the results recapitulation of the bill of sale to see the total units sold of each item. Resulting piled of inventory.From the problems, with the sales turnover of information systems that can be detailed by type of goods, name of goods, brand and size by using the sell-through method can help existing problems. The process of calculating the value of sales turnover of goods is by dividing the sales units with units of Goods Available for Sale .Reporting from the system are reported sales turnover of goods that can be detailed by type of goods, name of goods, brand and size. With a sales turnover information system, can help Asri Busana Stores in planning the purchase of goods.